Bile Salt 3α- and 12α-Hydroxysteroid Dehydrogenases from Eubacterium lentum and Related Organisms - Macdonald, Ian A. (1979)
Thirty-two strains of Eubacterium lentum and phenotypically similar anaerobic gram-positive bacilli were screened for intracellular bile salt 3α- and 12α-hydroxysteroid dehydrogenase (HSDHase) activities. These organisms were categorized into four groups: (A) those containing 12α-HSDHase only (10 strains), (B) those containing 3α- and 12α-HSDHase (13 strains), (C) those containing 3α-HSDHase only (2 strains), and (D) those devoid of any measurable HSDHase activity (7 strains). Of the respective four groups, 9/10, 13/13, 0/2, and 0/7 were like the neotype strain of E. lentum (ATCC 25559) in that they produced H(2)S in a triple sugar iron agar butt, reduced nitrate to nitrite, and weakly decomposed hydrogen peroxide. The other strains were variable for nitrate reduction and activity on hydrogen peroxide, but all the organisms in the first three categories (with one exception) were H(2)S producers (triple sugar iron agar butt) and all (with one exception) were designated E. lentum, whereas the organisms of category B were non-H(2)S producers (triple sugar iron agar butt). Five of these seven were not stimulated by arginine and are designated “phenotypically similar organisms.” Thin-layer chromatography of extracted spent bacterial medium of four representative strains from each group grown in the presence of cholate revealed the presence of (A) 12-oxo product, (B) 12-oxo and 3-oxo products, (C) 3-oxo product, and (D) the absence of any of these products. The 12α-HSDHase of category B organisms was unstable unless 10(−3) M dithioerythritol was added to the buffer. With the exception of 3 out of 32 strains, there was a positive correlation between the production of measurable amounts of 12α-HSDHase and H(2)S production. Growth curves and the effect of arginine on growth and the production of 3α- and 12α-HSDHase were examined in representative strains of categories A, B, and C. Both enzymes were shown to bind onto a nicotinamide adenine dinucleotide-Sepharose column and could be eluted by high-ionic-strength buffer, resulting in approximately 25-fold and 18-fold purification, respectively. Molecular weight estimations by Sephadex G-200 gave values of 205,000 and 125,000 for the 3α- and 12α-HSDHase, respectively. Purified 12α-HSDHase was investigated with respect to pH requirement, substrate specificity, and enzyme kinetics.